2017
DOI: 10.5539/ijps.v9n4p44
|View full text |Cite
|
Sign up to set email alerts
|

Posture and Social Problem Solving, Self-Esteem, and Optimism

Abstract: When feeling powerful humans and other animals display expansive postures, but can posing in expansive and powerful postures also generate empowerment? Researchers have studied the "power posing effect" the concept that powerful expansive postures generate empowerment, and found conflicting evidence. Some evidence of power posing's impact shows increased hormones and a variety of behaviors indicating greater confidence. Yet still others have found no effect on hormones or behaviors, and suggest the impact of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Further, LPPs elicited negative mood (Rossberg‐Gempton & Poole, 1993) and guilt (Rotella & Richeson, 2013). By contrast, various authors (Davis et al, 2017; Jackson, Nault, Smart Richman, LaBelle, & Rohleder, 2017; Miragall, Etchemendy, Cebolla, Rodriguez, Medrano, & Baños, 2018; 4 Saggese et al, 2018) found no effects of poses on emotions, social anxiety, or vitality, and Nielsen (2017) reported no difference in optimism between people adopting HPPs versus LPPs. Finally, in chronically powerless people, HPPs elicited more vengeance than LPPs (Strelan, Weick, & Vasiljevic, 2014).…”
Section: Effects On the Actormentioning
confidence: 97%
See 1 more Smart Citation
“…Further, LPPs elicited negative mood (Rossberg‐Gempton & Poole, 1993) and guilt (Rotella & Richeson, 2013). By contrast, various authors (Davis et al, 2017; Jackson, Nault, Smart Richman, LaBelle, & Rohleder, 2017; Miragall, Etchemendy, Cebolla, Rodriguez, Medrano, & Baños, 2018; 4 Saggese et al, 2018) found no effects of poses on emotions, social anxiety, or vitality, and Nielsen (2017) reported no difference in optimism between people adopting HPPs versus LPPs. Finally, in chronically powerless people, HPPs elicited more vengeance than LPPs (Strelan, Weick, & Vasiljevic, 2014).…”
Section: Effects On the Actormentioning
confidence: 97%
“…With respect to state self‐esteem, there were also effects of HPPs (Klenner, Otto, & Asbrock, 2016; Körner, Köhler, & Schütz, 2020; Körner, Petersen, & Schütz, 2019) but there were no effects on trait self‐esteem (Kwon & Kim, 2015; Nielsen, 2017). Further, LPPs elicited negative mood (Rossberg‐Gempton & Poole, 1993) and guilt (Rotella & Richeson, 2013).…”
Section: Effects On the Actormentioning
confidence: 99%
“…These three studies observed either a change only after expansive postures (Bohns & Wiltermuth, 2012;Lee & Schnall, 2014) or no significant effect (Jamnik & Zvelc, 2017). Similarly, only four studies included a control group, and observed a significant difference only for the constrictive posture (Cesario & McDonald, 2013) or no significant effects (Davis et al, 2017;Nielsen, 2017;Smith & Apicella, 2017). Thanks to the reasonably high statistical power and to the within-subject design of the current study, we can be more confident that the observed posture effects did not originate from baseline between-group differences in approach and avoidance tendencies.…”
Section: Discussionmentioning
confidence: 59%
“…Second, the majority of studies on other postural feedback effects used explicit self-reports (Kozak et al, 2014;Nielsen, 2017;Peña & Chen, 2017;Rotella & Richeson, 2013;Strelan et al, 2014). The posture effect on explicit feelings of power in a meta-analysis of six pre-registered and highly-powered studies (Gronau et al, 2017) was larger in subjects familiar with "power posing"., suggesting that explicit self-reports are susceptible to demand effects.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with positive self-esteem believe that they are valuable people, view stress more positively, and can solve various problems in their lives (Hall, Crutchfield, & Jones, 2018). This self-validation effect encourages individuals to display various behaviors that are believed to be good for them (Nielsen, 2017), including one of which is social problem-solving. The research of Cong, Ling, and Aun (2019) states that individuals with high self-esteem tend to do problemfocused coping.…”
Section: Resultsmentioning
confidence: 99%